Mediating effect of big data analytics on project performance of small and medium enterprises. Issue 1 (2nd July 2020) - Mangla, Sachin K.; Raut, Rakesh; Narwane, Vaibhav S.; Zhang, Zuopeng (Justin); priyadarshinee, Pragati
Abstract : Purpose: This study aims to investigate the mediating role of "Big Data Analytics" played between "Project Performance" and nine factors including top management, project knowledge management focus on sustainability, green purchasing, environmental technologies, social responsibility, project operational capabilities, project complexity, collaboration and explorative learning, and project success. Design/methodology/approach: A sample of 321 responses from 106 Indian manufacturing small and medium-scaled enterprises (SMEs) was collected. Data were analyzed using empirical analysis through structural equation modeling. Findings: The result shows that project knowledge management, green purchasing and project operational capabilities require the mediating support of big data analytics. The adoption of big data analytics has a positive influence on project performance in the manufacturing sector. Practical implications: This study is useful to SMEs managers, practitioners and government policymakers to develop an understanding of big data analytics, eliminate challenges in the adoption of big data, and formulate strategies to handle projects efficiently in SMEs in the context of Indian manufacturing. Originality/value: For the first time, big data for manufacturing firms handing innovative projects was discussed in the Indian SME context.